Het ons kerkwees in strukture gestol? - Spoelstra, B. (Hervormde teologiese studies, 1986)
Does the church freeze in structures? Indications worldwide reveal that no clear and distinct concept of the church prevails today. It is maintained that a dynamic concept of the church and ministerial view on ecclesiastical institutions gave way during the Enlightenment to the concept of the church as a fixed formal institution or a legally defined structure. Even the Reformation wanted to reform papacy and not to establish church structures in opposition to Rome. The structural and denominational view of the church triggered off recurrent church schisms and on the other hand gave birth to an overwhelming urge to unify and form worldwide ecumenical structures, whereby local diversities are even called sin. The question is raised: By retaining the dynamic concept of the church as humans, people of God, wouldn't a new perspective be opened on the problem of diversities?